PENGARUH GAYA KEPEMIMPINAN KEPALA SEKOLAH DAN PROFESIONALISME GURU TERHADAP PRESTASI BELAJAR TAHFIDZ PESERTA DIDIK SMA AL-WILDAN ISLAMIC BOARDING SCHOOL - Candra, Candra (el-Moona: Jurnal Ilmu Pendidikan Islam, 2023)
This study aims to determine and test empirical data related to Leadership Style and Teacher Professionalism on Tahfidz Learning Achievement separately or simultaneously. Data analysis techniques using descriptive analysis models, correlation coefficients, simple regression analysis and multiple regression. The type of analysis used is correlation analysis and simple regression and multiple regression which is described descriptively. This is evidenced by the results of the correlation coefficient (r) of the Leadership variable (X1) with the Learning Achievement variable Tahfidz Qur'an (Y) obtained Pearson values correlation (ry1) of 0.525 and the coefficient of determination R2 (R square) of 0.276. While the results of the simple regression analysis show the regression equation (unstandardized coefficients B) Ŷ = 55.282+ 0.303 X1, there is a positive and significant effect of teacher professionalism on learning achievement in Tahfidz Qur'an. This is evidenced by the results of the coefficient value of the variable Teacher Professionalism (X2) with Tahfidz Qur'an Learning Achievement (Y) obtained a Pearson correlation (ry2) value of 0.623 and a coefficient of determination R2 (R square) of 0.388. While the results of the simple regression analysis show the regression equation (unstandardized coefficients B) Ŷ = 37.257 + 0.492 X2, there is a positive and significant influence between the Principal's Leadership Style and Teacher Professionalism together on Learning Achievement Tahfidz Qur'an. This is proven by the magnitude of the influence which can be seen from the results of the determination coefficient R2 (R square) of 0.410 and the results of multiple regression analysis carried out together, showing the regression equation (unstandardized coefficients B) Ŷ = 37.361+0.387 X1+ 0.116 X2.